What about the Rest of Them? Fatal Injuries Related to Production Agriculture Not Captured by the Bureau of Labor Statistics (BLS) Census of Fatal Occupational Injuries (CFOI). Issue 1 (2nd January 2022) - Weichelt, Bryan; Scott, Erika; Burke, Rick; Shutske, John; Gorucu, Serap; Sanderson, Wayne; Madsen, Murray; Redmond, Emily; Murphy, Dennis J.; Rautiainen, Risto
ABSTRACT: Surveillance of injuries in production agriculture is necessary to inform stakeholders about workplace hazards and risks in order to improve and advance injury prevention policies and practices for this dangerous industry. The most comprehensive fatal injury surveillance effort currently in the United States is the Bureau of Labor Statistics (BLS) Census of Fatal Occupational Injuries (CFOI), which covers occupational fatalities in all U.S. industries, including production agriculture. However, this surveillance does not include many categories of fatalities that occur during agricultural work or on production agriculture worksites. To better capture the human cost of production agriculture, the authors of this paper call for the collection of additional data with a broader scope that supplements, not replaces, the current CFOI. This paper describes challenges in surveillance, highlights key procedural gaps, and offers recommendations for advancing national surveillance of fatal traumatic injuries associated with production agriculture.